Prevalence of depressive symptoms and their associated factors among older adults in Yirgalem town, Southern Ethiopia: A community-based cross-sectional study - Mulugeta, Abiy; Azale, Telake; Mirkena, Yohannes; Koye, Selam; Nakie, Girum; Kassaye, Abenet; Dereje, Jerman; Bedewi, Neim; Dechasa, Deribe Bekele; Asfaw, Henock (Frontiers in Psychiatry, 2023)
Background: Depression is a serious mental health issue and the largest contributor to disability worldwide. Elderly people with depression are significantly more likely to experience negative outcomes such as poor physical health, strained social relationships, and decreased quality of life. Studies on geriatric depression are limited in developing nations like Ethiopia. Objectives: The purpose of this study was to determine the prevalence of depressive symptoms and associated factors among older adults in Yirgalem, Southern Ethiopia, in 2022. Methods: Community based cross-sectional study was conducted among a sample of 628 older adults at Yirgalem town from May 15 to June 15, 2022. The study subjects were selected using a multi stage systematic sampling technique. Data were collected by using Geriatric depression scale 15 through face-to-face interview. The collected data was edited, cleaned, coded, and entered into Epi data version 4.6 software and analysed using STATA version 14. Bivariable and multivariable logistic regression analysis was computed to identify factors associated with depression and statistical significance was declared at 95% confidence interval with P-value less than 0.05. Results: A total of 620 older adults were included in the study, with a response rate of 97.8%. The prevalence of depressive symptoms among older adults was 51.77% (95% CI: 47.83-55.69). Being a female (AOR = 2.3, 95% CI: 1.56-3141), more advanced age 70-79 year (AOR = 1.92, 95% CI: 1.20-3.07), 80-89 year (AOR = 2.15, 95% CI: 1.27-3.65), 90 and older (AOR = 3.77, 95% CI: 1.95-7.79), living alone (AOR = 1.99, 95% CI=1.17-3.41), having a chronic illness (AOR = 3.24, 95% CI: 1.06-4.46), anxiety (AOR = 3.40; 95% CI: 2.25-5.14), and having poor social support (AOR = 3.56, 95% CI: 2.09-6.04) were statistically associated with depressive symptoms at P-value less than 0.05. Conclusion: In this study, depression affects more than half of the elderly residents in the study area. more advanced age, being a woman, living alone, having a chronic illness, having anxiety, and having poor social support were all strongly linked to depression. There is a necessity for integrating the community healthcare system with counselling and psychiatric services.